Propuesta de modificación de la estructura de sanciones del Reglamento de Infracciones y Sanciones de la Superintendencia Nacional de Educación Superior Universitaria - Sunedu - Robles Chang, Lino Andrés (2019)
The present professional sufficiency work entitled "Proposal of modification of the structure of sanctions of the Regulation of Infractions and Sanctions of the National Superintendence of Higher Education University - Sunedu" collects the concepts and economic theories used in the development of the professional activity performance, as well as like the investigations and economic proposals made in relation to the improvement of the public regulation exerted by the Sunedu towards the administered ones of its competition. It raises the main objective of informing about the activities and tasks carried out in the development of a solution proposal to the problem identified about to the different impacts resulting from the application of the current sanctions structure of the Sunedu according to the economic and financial characteristics of each administered. In addition, as a result of the aforementioned research activities, a better understanding of the regulated market and the design of an objective graduation methodology for sanctions was obtained, as well as a proposal for a structure of sanctions to homogenize the impact of its application on its different administered.